Relationship between Remittance and Credit Disbursement of the Banking Sector: A Study from Bangladesh - Muktadir-Al-Mukit, Dewan; Islam, Nazrul (Journal of Business and Management Research, 2016)
The paper investigates the relationships of remittance with credit disbursement of the banking sector in Bangladesh. The major portion of the remittance in Bangladesh is transferred through different banks as official channel. Besides, remittance recipient families transfer a portion of the remittance in the deposit accounts of different commercial banks. This two-way process helps to increase the liquidity position of the bank that enables them to increase the credit disbursement position of the banks. Moreover, the use of this loan by the business entrepreneurs indirectly helps economic development of Bangladesh. This study uses time series econometric techniques with monthly data spanning from 1976 to 2012 to explore the relationships between the remittances and the credit disbursements of the banks. The findings of the study clearly show that remittances assist to enhance the amount of credit disbursements of the banking sector in Bangladesh. The normalized co-integrating coefficients are found statistically significant and show a stable and positive relationship between the variables under this study. Finally, Granger causality analysis suggests the existence of bidirectional causality between remittances and credit disbursements. Journal of Business and Management Studies Vol.1(1) 2016: 39-52